Synthesis and characterization of mononuclear cobalt(II), nickel(II), copper(II), zinc(II), cadmium(II) and dinuclear uranyl(VI) complexes with N,N-bis(2-{[(2,2-dimethyl-1,3-dioxolan-4-yl)methyl]amino}butyl) N?,N?-dihydroxyethanediimidamide - Canpolat, E; Yazici, A; Kaya, M (Springer, 2006)
In this study, the new vic-dioxime ligand (LH2) and its complexes with Co-II, Ni-II, Cu-II, Zn-II, Cd-II and UO2VI are described. The structures of these complexes were characterized by elemental analyses, i.r., H-1- and C-13-n.m.r. spectra, u.v.-vis. spectroscopy, magnetic susceptibility measurements, conductivity measurements and thermogravimetric analyses (t.g.a.).
Keywords: Vic-Dioxime; Metal-Complexes; Cd(Ii) Complexes; Ni(Ii); Cu(Ii); Ligands; Zn(Ii); Co(Ii); Oxime; Reactivity